Potential Therapeutic Benefits of Honey in Neurological Disorders: The Role of Polyphenols - Arslan Iftikhar; Rimsha Nausheen; Humaira Muzaffar; Muhammad Ahsan Naeem; Muhammad Farooq; Mohsin Khurshid; Ahmad Almatroudi; Faris Alrumaihi; Khaled S. Allemailem; Haseeb Anwar (Molecules, 2022)
Honey is the principal premier product of beekeeping familiar to Homo for centuries. In every geological era and culture, evidence can be traced to the potential usefulness of honey in several ailments. With the advent of recent scientific approaches, honey has been proclaimed as a potent complementary and alternative medicine for the management and treatment of several maladies including various neurological disorders such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and multiple sclerosis, etc. In the literature archive, oxidative stress and the deprivation of antioxidants are believed to be the paramount cause of many of these neuropathies. Since different types of honey are abundant with certain antioxidants, primarily in the form of diverse polyphenols, honey is undoubtedly a strong pharmaceutic candidate against multiple neurological diseases. In this review, we have indexed and comprehended the involved mechanisms of various constituent polyphenols including different phenolic acids, flavonoids, and other phytochemicals that manifest multiple antioxidant effects in various neurological disorders. All these mechanistic interpretations of the nutritious components of honey explain and justify the potential recommendation of sweet nectar in ameliorating the burden of neurological disorders that have significantly increased across the world in the last few decades.